Northwest history. Mining. Machinery & equipment. 1921-06-07 (1921)
New compressor for the friend - William Schierding, manager of the Friend Mining company, of Spokane, is inspecting the property in the Beaver creek district of the Coeur d'Alenes. The company had a small compressor, which it found inadequate, and will now purchase a larger one with which to continue operations this summer.